2018
DOI: 10.1158/1940-6207.capr-17-0309
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity at Age 10 and Mammographic Density among Premenopausal Women

Abstract: Although childhood adiposity is inversely associated with breast cancer risk, the association of childhood adiposity with mammographic density in premenopausal women has not been adequately studied. We analyzed data from 365 premenopausal women who came in for screening mammography at Washington University (St. Louis, MO) from 2015 to 2016. Body size at age 10 was self-reported using somatotype pictogram. Body mass index (BMI) at age 10 was imputed using data from Growing Up Today Study. Volpara software was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Possible measurement error in the assessment of childhood body size in our study, which relied on recalled body size at age 10 by women in their midlife, is a serious limitation. We used a pictogram, developed by Stunkard et al (29), and used in large studies of breast cancer risk and mammographic density (16,21), which has been shown to have less measurement error than recalled weight (47,48). A prior study reported a high correlation (0.70) between measured BMI at age 10 and recalled body size at age 10 using this pictogram in elderly adults (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible measurement error in the assessment of childhood body size in our study, which relied on recalled body size at age 10 by women in their midlife, is a serious limitation. We used a pictogram, developed by Stunkard et al (29), and used in large studies of breast cancer risk and mammographic density (16,21), which has been shown to have less measurement error than recalled weight (47,48). A prior study reported a high correlation (0.70) between measured BMI at age 10 and recalled body size at age 10 using this pictogram in elderly adults (28).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood and adolescent body size, which have been associated with lower premenopausal and postmenopausal breast cancer (1214), may influence breast cancer risk by leaving their mark on breast tissue development and composition (15). The growing research on early life body size influences on adult MBD is characterized by an abundance of measurement methods for MBD and for early life body size as well as variation for the age at which body size is assessed (1621). While collectively the evidence to date point to an inverse association between childhood body size and MBD in postmenopausal women, less is known about whether childhood body size and MBD associations are seen in premenopausal women, particularly across women that may have had different childhood environments.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, the Stunkard 9-level figure pictogram was categorized into four groups: (i) body size 1 or 2; (ii) body size 3 or 4; (iii) body size 5; and (iv) body size 6 or higher. We estimated BMI at age 10 using BMI and Stunkard pictograms, both provided at age 10, from the Growing Up Today Study (21,22). Because the Stunkard 9-level figure somatotype pictogram for girls in the Growing Up Today Study ranged from 1 to only 7, we did not compute BMI at age 10 for 10 women in our study, whose body sizes at age 10 were larger than 7 (8 or 9).…”
Section: Adiposity Measures and Adiposity Changementioning
confidence: 99%
“…We recruited 383 premenopausal women who were scheduled for an annual screening mammography at the Joanne Knight Breast Health Center at the Washington University School of Medicine, and Siteman Cancer Center, St. Louis, MO in 2016. Detailed description of the study population has been provided previously (22). Complete mammographic density data and blood samples were available for 375 women.…”
Section: Methodsmentioning
confidence: 99%